2022
DOI: 10.1002/slct.202200415
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Zinc Oxide Nanoparticles Mediated fromCassia renigeraBark and Detect Its Effects on Four Varieties of Rice

Abstract: The present study reports a cost‐effective and environmentally benign method for biogenic synthesis of ZnO nanoparticles (NPs) using Cassia renigera bark extract (CRBE) and evaluation of its effect on four rice varieties (PR 7, basmati 1509, HR 47, and sharbati). The physicochemical characterisation of CRBE: ZnO NPs was carried out using X‐ray diffractometer (XRD), Field emission scanning electron microscope (FESEM) and UV‐Vis spectrophotometer. Structural investigation using Rietveld refinement method reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 52 publications
0
0
0
Order By: Relevance
“…Similarly, ref. [74] observed that ZnSO 4 NPs, when combined with the Pseudomonas spp. PGPB, boosted the levels of zinc, potassium, phosphorus, and nitrogen in rice plants.…”
Section: Major Nanoparticles Used In Agriculturementioning
confidence: 99%
“…Similarly, ref. [74] observed that ZnSO 4 NPs, when combined with the Pseudomonas spp. PGPB, boosted the levels of zinc, potassium, phosphorus, and nitrogen in rice plants.…”
Section: Major Nanoparticles Used In Agriculturementioning
confidence: 99%